Dual effects of entomopathogenic fungi on control of the pest Lobesia botrana and the pathogenic fungus Eutypella microtheca on grapevine - Aguilera Sammaritano, Juan Alberto (2021)
Background: Entomopathogenic fungi (EPF) are the natural enemies of insect pests. Nevertheless, research on the use of EPF for simultaneous prevention of pest and disease agents on the same crop is limited. In this study, we explored the potential dual effects of three strains of the EPF Metarhizium anisopliae on the control of detrimental agents of Vitis vinifera L., including different developmental stages (larvae, pupae, and adult) of the insect pest Lobesia botrana and the phytopathogenic fungus Eutypella microtheca. Methods: Laboratory pathogenicity trials were performed to examine the effects of the three M. anisopliae strains on the mortality rate of L. botrana. In addition, field trials were conducted to assess the biocontrol potential of one selected M. anisopliae strain on the larval stage of L. botrana. Moreover, inhibitory effects of the three EPF strains on E. microtheca growth were examined in vitro. Results: All the M. anisopliae strains were highly effective, killing all stages of L. botrana as well as inhibiting the growth of E. microtheca. The in vitro mortality of larvae treated with the strains was over 75%, whereas that of treated pupae and adults was over 85%. The three EPF strains showed similar efficacy against larvae and adult stages; nevertheless, pupal mortality was observed to be strain dependent. Mortality of L. botrana larvae ranged from 64 to 91% at field conditions. Inhibition of E. microtheca growth reached 50% in comparison to the control. Conclusions: Our study showed that M. anisopliae strains were highly effective in ensuring control of two different detrimental agents of V. vinifera L., providing new evidence to support the dual effects of entomopathogenic fungi.